Preparation and characterization of ultrasound-assisted nanoemulsions containing natural oil for anti-aging effect - Kanokwan Kiattisin; Panithan Srithongchai; Warunchana Jaiyong; Korawinwich Boonpisuttinant; Warintorn Ruksiriwanich; Pensak Jantrawut; Mathukorn Sainakham (Journal of Agriculture and Food Research, 2024)
This research investigated the properties including appearance, rheology, peroxide value and bioactivities of three types of natural oils. Ultrasound-assisted nanoemulsions of the selected natural oils were prepared, evaluated for physical appearance, droplet size, polydispersity index, zeta potential using Zetasizer®, turbidity change measured by UV-VIS spectrophotometer and observed after stability test. After that, nanoemulsions with a particle size less than 200 nm will be selected and evaluated for cytotoxicity and collagen biosynthesis on human skin fibroblasts. The result showed that avocado oil gave the lowest peroxide value and IC50 value by ABTS assay at 6.65 and 30.50 ± 0.98 μg/ml, respectively. Finally, avocado oil, which showed moderate anti-aging activity, was chosen to develop nanoemulsions by an ultrasonic processor. The best nanoemulsion formulation, PS21, contained 8 % avocado oil, 7.5 % PEG 40 hydrogenated castor oil and 2.5 % Span 80 with a small droplet size, narrow polydispersity index and high zeta potential at 68.30 ± 3.08 nm, 0.24 ± 0.08, and −55.10 ± 2.66 mV, respectively. After the stability test, PS21 presented a good physical appearance with no phase separation, an acceptable range of droplet size, a narrow size distribution and slightly changed zeta potentials and turbidity. In the cell culture experiment, cell viability was greater than 80 % for all selected nanoemulsions at a concentration of 0.1 % v/v in comparison to the control group. However, collagen stimulation ranging from 2.27 ± 0.25 to 16.67 ± 2.30 % was observed in only four nanoemulsions, or 50 % of the total sample group. PS21 at a concentration of 0.1 % v/v gave the highest collagen stimulation with no cytotoxicity in human skin fibroblasts. According to all results, avocado oil can be formulated into nanoemulsions with good appearance and stability that are suitable for the further development of novel foods and health care products.